Investigation on Numerical Simulation of Chloride Transport in Unsaturated Concrete - Qingzhang Zhang (Hindawi Limited, 2021)
Marine atmosphere environment accelerates the process of chloride penetration into concrete under the coupling effect of ambient temperature and relative humidity, thereby reducing the durability and service life of concrete. This paper aims to investigate the change of water equilibrium saturation and the chloride transport properties of concrete materials in different environments. The water equilibrium saturation tests at three temperatures and five relative humidity (RH) and salt spray erosion tests at three temperatures were performed. The influence of RH and temperature on the equilibrium saturation of concrete and the influence of temperature and time on the chloride diffusion coefficient are investigated. The results show that, in the process of moisture absorption and desorption, the equilibrium saturation of concrete gradually decreases as temperature rises. At the same depth of concrete, the chloride content gradually increases with temperature increasing, as well as the chloride diffusion coefficient. However, as the corrosion time of salt spray increases, the altering of chloride diffusion coefficient becomes less. Based on the Kelvin equation, a relationship between capillary pressure and water saturation in concrete was established, and a moisture transfer model for concrete in the process of moisture absorption and desorption was derived. Further, based on the established chloride diffusion equation and heat balance equation, a model of temperature-wet-chloride coupling chloride transfer was derived. Theory model simulation results show the transfer speed of chloride under the coupling of diffusion and capillary is higher than pure diffusion in moisture in the absorption process. However, the opposite is true in the desorption process. Moreover, with the increment of saturation rate, the capillary effect on chloride transport is enhanced.